Reimagining Sharīʿah for Contemporary Societies: Authority, Governance, and Human Well-Being - Muhammad Latif Fauzi (Faculty of Sharia, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The study of Islamic law (Sharīʿah) has entered a period of significant transformation, moving beyond its treatment as a historically fixed legal tradition toward engagement with contemporary social, technological, and institutional challenges. Digitalization has reshaped religious authority, knowledge dissemination, and devotional practices, while innovations such as financial technology, artificial intelligence, and blockchain have created legal questions requiring renewed Sharīʿah reasoning grounded in both classical jurisprudence and modern expertise (Alqurashi et al., 2026; Kumar & Sahu, 2026; Lussi et al., 2024; Tran, 2026). At the same time, constitutional developments across Muslim-majority countries continue to redefine the relationship between Islamic law and state governance.